2023
DOI: 10.1186/s12905-023-02397-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between mental health and climacteric adjustment in middle aged women: a confirmatory analysis

Abstract: Background Climacteric changes in women are associated with an increased probability of psychological symptoms. Identifying the relationship between adjustment to this period and mental health helps to plan for middle-aged women’s health improvement. Therefore, the present study aimed to investigate the relationship between climacteric adjustment (CA) and mental health in middle aged women. Method This cross-sectional study was conducted on 190 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This was surprising, as older age of menopause onset means longer exposure to endogenous estrogens, which was associated with a lower risk of depression later in life 27 . A recent cross-sectional study showed that middle-aged women with decreased climacteric adjustment, or social-emotional adjustment to perimenopause/menopause, had increased psychological symptoms 28 . One possible explanation for our finding is that women who have passed the transitional phase of the perimenopause have readjusted, hence perceiving less psychological distress a few years after menopause.…”
Section: Discussionmentioning
confidence: 99%
“…This was surprising, as older age of menopause onset means longer exposure to endogenous estrogens, which was associated with a lower risk of depression later in life 27 . A recent cross-sectional study showed that middle-aged women with decreased climacteric adjustment, or social-emotional adjustment to perimenopause/menopause, had increased psychological symptoms 28 . One possible explanation for our finding is that women who have passed the transitional phase of the perimenopause have readjusted, hence perceiving less psychological distress a few years after menopause.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety, depression, and impairment in social functioning may result because of climacteric maladjustment. [ 35 ]…”
Section: Effects Of Menopause On Quality Of Lifementioning
confidence: 99%